Post-Ganglionic Sympathetic Neurons can Directly Sense Raised Extracellular Na+ via SCN7a/Nax - Davis, Harvey; Paterson, David J; Herring, Neil (Frontiers in Physiology, 2022)
The relationship between dietary NaCl intake and high blood pressure is well-established, and occurs primarily through activation of the sympathetic nervous system. Nax, a Na+-sensitive Na+ channel, plays a pivotal role in driving sympathetic excitability, which is thought to originate from central regions controlling neural outflow. We investigated whether post-ganglionic sympathetic neurons from different ganglia innervating cardiac and vasculature tissue can also directly sense extracellular Na+. Using whole-cell patch clamp recordings we demonstrate that sympathetic neurons from three sympathetic ganglia (superior cervical, stellate and superior mesenteric/coeliac) respond to elevated extracellular NaCl concentration. In sympathetic stellate ganglia neurons, we established that the effect of NaCl was dose-dependent and independent of osmolarity, Cl- and membrane Ca2+ flux, and critically dependent on extracellular Na+ concentration. We show that Nax is expressed in sympathetic stellate ganglia neurons at a transcript and protein level using single-cell RNA-sequencing and immunohistochemistry respectively. Additionally, the response to NaCl was prevented by siRNA-mediated knockdown of Nax, but not by inhibition of other membrane Na+ pathways. Together, these results demonstrate post-ganglionic sympathetic neurons are direct sensors of extracellular Na+ via Nax, which could contribute to sympathetic driven hypertension.